Effects of Hyperbaric Oxygen Therapy on Hypertensive Patients - chandra, roderick; djiuardi, evelyn; fatoni, patmah (Liaison Journal of Engineering, 2024)
The scope of this research is to determine the affect of hyperbaric oxygen therapy to patients of Asyifa hyperbaric clinic that suffers from hypertension. There are 20 participants participate thisresearch with the range of their age between 31-76 years old, along with various kind of sleep duration in between 5,5 – 10 hours of sleep. Some of the patients took medicine for hypertension or any other disease that related to the other disease. Participants of Asyifa Hyperbaric Clinic that participate this research have done at least 5 times of conducting hyperbaric oxygen therapy. This research will involve of using statistical packages for social science program (SPSS) The results of paired t test shows that the N value are the correlation on blood tension systole shows 0.951, while the correlation on blood tension diastole shows 0.916. If the correlation value is closeto 1,000 then it shows that there is a correlation effect of hyperbaric oxygen therapy on hypertension. This shows that HBOT does affecting patients that has hypertension and it helps lowering down high blood pressure. Keywords: Hypertension, Hyperbaric Oxygen Therapy, Liaison Journal of Engineering; International University Liaison Indonesia